2009
DOI: 10.1111/j.1365-2893.2009.01224.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemerin, vaspin and insulin resistance in chronic hepatitis C

Abstract: Adipocytokine profile seems to play a distinct role in the pathogenesis of chronic hepatitis C (CHC). Chemerin and vaspin are recently described adipocytokines with various suggested functions and potential to modulate inflammatory response and insulin resistance (IR). We assessed chemerin, vaspin and leptin serum concentration and studied their association with IR laboratory and morphological features in patients with hepatitis C. The study included 40 patients with hepatitis C and 20 healthy volunteers, simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
71
2
10

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 33 publications
11
71
2
10
Order By: Relevance
“…Our study did not disclose a significant relationship between a serum vaspin level and insulin resistance (HOMA-IR), but we registered a tendency to higher serum vaspin in patients with HOMA-IR above 3. On the other hand, HOMA-IR was significantly associated with the stage of fibrosis supporting earlier findings that insulin resistance is one of important contributors to liver fibrosis in CHC [3,8,15].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our study did not disclose a significant relationship between a serum vaspin level and insulin resistance (HOMA-IR), but we registered a tendency to higher serum vaspin in patients with HOMA-IR above 3. On the other hand, HOMA-IR was significantly associated with the stage of fibrosis supporting earlier findings that insulin resistance is one of important contributors to liver fibrosis in CHC [3,8,15].…”
Section: Discussionsupporting
confidence: 87%
“…Generally, the serum vaspin showed a positive association with the fibrosis stage, being in patients with advanced fibrosis almost as high as in controls. In our previous study we showed a tendency to elevated serum vaspin levels in CHC patients with septal fibrosis, however, that study was carried out on a smaller group of patients, not covering the whole spectrum of fibrosis stages [15].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Steatosis was positively related tofibrosisstageandIR.HOMA-IRwassignificantly higherinpatientswithgrade0thanintherestofthe patients.Moreover,thedifferencewasstillsignificant comparingpatientswithgrade0and1tothosewith grade2and3ofsteatosis.Similarly,analysisofmRNA vaspinlevelsinthelivertissueshowedamarkeddifference with the higher intensity in patients with lipidstorageaffectingmorethan5%ofhepatocytes. Additionalanalysisrevealedfurtherincreaseofvaspin mRNA in patients with greater extent of steatosis, but the difference did not reach statistical significance.Theseresultsareinaccordancewithfindings of our previous studies regarding vaspin serum lev- The next histopathological feature included into thescoringsystemfordiagnosisofNASHishepatocyteballooning [31].Inourstudy,itsgradewasassociatedwithgradeoflobularinflammationandsteatosis.OurpreviousstudyinCHCpatientsshowed anegativerelationshipbetweenhepatocyteballooningandserumvaspinlevels [30].Incontrast,inNA-FLD serum vaspin levels were positively associated withhepatocyteballooning [27].However,themost recentstudydidnotfindsucharelationship [28].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with chronic hepatitis C serum chemerin is strongly increased and this may be related to higher hepatic and/or adipocyte synthesis and / or inappropriate clearance of this protein from the circulation. Of note, in these patients systemic chemerin is even negatively associated with hepatic necro-inflammatory grade [31].…”
mentioning
confidence: 88%